Didactics Planning in University Education during pandemics times - Kenski, Vani Moreira (2022)
This article presents results of exploratory research on the teaching planning process of university professors during the pandemic. Its objective was to identify the characteristics of a new pedagogical practice, digitally mediated, from the teachers' perceptions in at least three remote offerings of their disciplines. The study was based on the responses of 25 university professors, from different areas of knowledge, about changes in their didactic plans to develop online activities during the pandemic. For the study, we, as authors, developed a questionnaire, made available on a virtual platform and answered by the professors. The responses – voluntary and anonymous – were numbered, analyzed and distributed into five categories – time; organization; practices; resources and interaction. The analysis of these categories was based on the qualitative constructivist perspectives of Charmaz (2008) for the Grounded Theory. From the analysis, we sought the thoughts of authors who dialogued with the analyzed aspects. In the end, we consider that the planning for the use of digital technologies in emergency situations of online teaching during the pandemic constituted changes in the teacher's thinking and action. They guided the development of immersive in-service training, generating transformations in the way these teachers teach. We also understand that digital culture, in rapid transformation, requires continuous digital didactic training, for the use of the most advanced technologies, according to the contexts and teaching objectives.